Evaluation of Simulated Snow and Snowmelt Timing in the Community Land Model Using Satellite‐Based Products and Streamflow Observations. (25th November 2018) - Toure, Ally M.; Luojus, Kari; Rodell, Matthew; Beaudoing, Hiroko; Getirana, Augusto
Abstract: The purpose of this study was to evaluate snow and snowmelt simulated by version 4 of the Community Land Model (CLM4). We performed uncoupled CLM4 simulations, forced by Modern‐Era Retrospective Analysis for Research and Applications Land‐only meteorological fields. GlobSnow snow cover fraction, snow water equivalent (SWE), and satellite‐based passive microwave snowmelt‐off day of year (MoD) data were used to evaluate snow cover fraction, SWE, and snowmelt simulations. Simulated runoff was then fed into a river routing scheme and evaluation was performed at 408 snow‐dominated catchments using gauge observations. CLM4 and GlobSnow snow cover extent showed a strong agreement, especially during the peak snow cover months. Overall there was a good correlation between simulated and observed SWE (correlation coefficient, R = 0.6). Simulated and observed SWE were similar over areas with relatively flat terrain and moderate forest density. The simulated MoD agreed (MoD differences [CLM4‐passive microwave] = ±7 days) with observations over 39.4% of the study domain. Snowmelt‐off occurred earlier in the model compared to the observations over 39.5% of the domain and later over 21.1% of the domain. Large differences of MoD were seen in the areas with complex terrain and dense forest cover. We also found that, although streamflow seasonal phase was accurately modeled ( R = 0.9), the peaks controlled by snowmelt were underestimated. Routed CLM4 streamflow tended to occur early (by 10 days on average). Key Points: The purpose of this study was to evaluate snow and snowmelt simulated by version 4 of the Community Land Model